Open spaces in public libraries: from social practices to cultural values - G. V. Varganova (Библиосфера, 2019)
The article considers the practice of creating open spaces in public libraries of foreign countries. Open space is a social phenomenon with a value load. The author emphasizes the role of open spaces in integrating social practices of the local community members, forming the territorial population identity, common values and cultural meanings. The paper highlights that it is necessary to use a wide range of traditional and virtual technologies in open spaces, as well as to strengthen cooperation with other social organizations. The role of open spaces is to socialize different demographic groups living at the same territory, to create conditions for their successful adaptation to the dynamically changing world and the socio-cultural potential reproduction. Open spaces create new opportunities for solving one of the most difficult task: they stimulate social activity of the local community members and form their cultural values. Thus, open spaces contribute to organizing interaction between different social groups living at the territory and strengthening the society sustainable structure.